Maximizing Career Growth Through the Influence of Popular Culture: An Exploration of Qualitative Research - Rammadan, Sastra; Lazuardini, Amanna Dzikrillah (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
Popular culture is a cultural form that develops in response to media exposure. That is, since the media can create cultural forms, people will accept them and turn them into cultural forms. Job development is the process of increasing one's capacity to work with the aim of pursuing a preferred occupation. The research was conducted using qualitative research methodology, as discussed in the research methodology sub-chapter. Qualitative research method is a type of research methodology that produces descriptive data through analysis of people's written or oral statements and observed behavior. Nasa Freak utilizes popular culture in his career development by marketing his work on several platforms that are often used by the community. The skills and knowledge gained through the experience of popular culture are such as making several combinations of songs or music that are rising in trend, then processed into several beats created by Nasa Freak himself. It can be concluded that there are specific skills and knowledge acquired by Nasa Freak itself through popular culture.